The Profile of Effective EFL Teachers: A Descriptive Study at Senior High Schools in Gowa - Dian Wahyu Restu; Haryanto Atmowardoyo; Mansur Akil (Universitas Negeri Makassar, 2018)
This research aimed at to find out the profile of effective EFL teachers based on four competences as stated in Permendiknas number 12 2007 at senior high school level; pedagogical competence, personal competence, social competence, and professional competence. This research employed descriptive qualitative research method. This research was conducted in SMAN 2 Tinggimoncong, SMAN 1Bajeng, and SMAN 1 Sungguminasa which were the three of the best and the most favorite state schools in Gowa Regency. The research subjects were EFL teachers. Before selecting the research subjects, a questionnaire with open responses was given to the all the third grade students in each school in order to find out their perceptions and opinions about their English teachers. Then, an English teacher who was mostly chosen by student was selected from each school as a research subject. Additionally, the second questionnaire was distributed to third graders to 10 students from each school to showed that two of three teachers classified as effective teachers in four competences.